Goal Orientation and Motives for Participation of Teacher-Coaches of Track and Field in Kuching Samarahan, Sarawak - Lim, Eng Hooi (2002)
The dependence on teacher-coaches for the bulk of the nation's athletic talent and the lack of sporting talent are matters of great concern. Frequently teacher-coaches become victims in efforts to find the causes even though there is a lack of research to understand the situation. This study described the goal-orientation and motives for participation of teacher-coaches of track and field in secondary schools in Kuching Samarahan, Sarawak as well as the characteristics of the coaching environment in these schools. The instruments utilized to measure the goal-orientation and the motives for participation were translated versions of the Task and Ego Orientation Questionnaire (TEOSQ; Shaharudin, 1998) and the Participation Motivation Questionnaire (PMQ; Khairuddin, 1998) respectively and modified to suit the participants. Pre-test of these versions were conducted with similar samples and yielded Cronbach reliability coefficients of .91 and .88 respectively. The results were obtained from 77 teacher coaches of track and field from 47 schools in Kuching Samarahan Division. The return rate was 81%. Results of the F -test showed that there were no statistically significant differences in goal orientation and motives for participation among the teacher-coaches of high performing, medium performing and low performing groups. Overall, 93% of the teacher-coaches were highly task-goal oriented. Skill Development (M = 4.64, SD = .48) was the most important factor affecting participation followed by Excitement/Challenge (M = 4.60, SD = .42). Recognition/Status was the least important (M = 3.00, SD = .83). All coaches in the study showed similar goal profiles and motivational tendencies. Bivariate correlations analysis revealed that, in general, task-goal orientation and intrinsic motivations were moderately and significantly correlated indicating a substantial relationship between the variables. Bivariate correlations also revealed that intrinsic motivation and extrinsic motivation were highly correlated indicating that while the participation of the teacher-coaches were significantly influenced by intrinsic motivational factors, extrinsic motives were also important. However, extrinsic factors had only a low correlation to ego-goal orientation. Together with the findings from the descriptive statistics, the study alerted us on the importance and impact of the coaching environment on teacher-coaches of largely similar goal orientation and motives for participation. If these teacher-coaches are to be effective introducers of their sport to students, the Ministry of Education must attend to creating an environment befitting the goal-orientation and motivation of the teacher-coaches. Implications for further practice and further research were discussed.